Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. (Policy Papers; Policy Paper ;, 2014)
TheaGlobal Policy Agenda (GPA)apresented to theaIMFC in April 2014aidentified a range of actions needed to transform the modest, uneven, and fragile recovery into more rapid, balanced, and sustainable growth. These actions included policies to manage monetary normalization and the associated policy spillovers and spillbacks; reforms to ensure robust growth while reducing vulnerabilities; and steps to facilitate external rebalancing. The GPA also outlined how the Fund would support the membership through assessments and policy advice provided in bilateral and multilateral surveillance, capacity building, and financial support.